2013
DOI: 10.1371/journal.pone.0078225
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of the Derived Neutrophil to Lymphocyte Ratio as a Prognostic Marker on a Large Cohort of Pancreatic Cancer Patients

Abstract: BackgroundWith growing evidence on the role of inflammation in cancer biology, the presence of a systemic inflammatory response has been postulated as having prognostic significance in a wide range of cancer types. The derived neutrophil to lymphocyte ratio (dNLR), which represents an easily determinable potential prognostic marker in daily practise and clinical trials, has never been externally validated in pancreatic cancer (PC) patients.MethodsData from 474 consecutive PC patients, treated between 2004 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 33 publications
1
72
0
Order By: Relevance
“…NLR was confirmed to be an independent prognostic biomarker in multivariate analysis, together with tumor stage, grade, administration of chemotherapy and high CRP [31]. NLR cut-off was initially set at 5, according to the previous literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NLR was confirmed to be an independent prognostic biomarker in multivariate analysis, together with tumor stage, grade, administration of chemotherapy and high CRP [31]. NLR cut-off was initially set at 5, according to the previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…There was no imbalance in KPS between GEM and GEMOXA group (KPS 80 or 90 in 53% and 42% of patients, respectively, chi-square p value = 0.209). Median BMI at treatment start was 23 (range [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Patients' Characteristics and Treatment Deliverymentioning
confidence: 99%
“…NLR is associated with tumor progression in pancreatic cancer. 34,35 Inflammatory cells accumulating between cancer cells play an important role in patient prognosis, because patients with lymphocyte infiltration around the tumor may have a better prognosis than those without infiltration patients. 36,37 Circulating IL-17-producing T cells release CXC chemokines recruiting neutrophils as well as promote the differentiation of tissue macrophages around the tumor into tumor-associated macrophages accelerating tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that a systemic inflammatory state is associated with the malignant biological behavior of the tumor (14,15). In particular, the neutrophil-lymphocyte ratio (NLR) has been evaluated as a predictor of prognosis in various types of solid tumor, including gastric, colorectal, pancreatic, breast and lung cancers (16)(17)(18)(19)). An elevated NLR has already been shown to be associated with poor prognosis in patients with HCC treated by liver transplantation, surgical resection, or TACE (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%